Asuhan Kebidanan Komprehensif pada Ny A Umur 22 Tahun dengan KEK dan CPD di PMB Ny S Wilayah Kerja Puskesmas Kaliwadas Tahun 2025 - tiara, Fera; Endang Susilowati; Surniah Surniah (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) can be a measure of a country's welfare in determining the optimal degree of health. The maternal mortality rate in the world is 303 thousand people (WHO 2023). MMR in Indonesia was 4,129 people in 2023. Meanwhile, the Infant Mortality Rate (IMR) in the world is 29,945 people (WHO, 2023). In Indonesia, there were 16.85 infant mortality rates in 2023. SEZ is a nutritional deficiency in pregnant women that lasts for several months or years. SEZ conditions can indirectly cause MMR and IMR. SEZ in pregnant women can cause complications such as IUGR, Abortion, LBW, Circulation, Anemia, Bleeding, and Childbirth complications. Research Objective: Providing Comprehensive Midwifery Care in accordance with midwifery care standards starting from pregnancy, childbirth, postpartum, newborn, and family planning in Mrs. A 22 years old with Chronic Energy Deficiency (SEZ) and Chepalo Pelvic Disproportion (CPD) with a midwifery management approach according to Varney and SOAP. Research Methods: Descriptive Qualitative with Case Study approach Results: Comprehensive Midwifery Care on Mrs. A aged 22 years with SEZ can be overcome by an increase in LILA, there is a CPD so that SC delivery is performed and appropriate case management is carried out so that labor, newborn, postpartum period, and family planning goes well. Conclusion: The results of the comprehensive care given to Mrs. A 22 years old with Chronic Energy Deficiency (SEZ) can be resolved marked by an increase in LILA, SC delivery on indications of CPD, normal LBW, normal postpartum, and mini pill birth control.